Perlindungan Hukum Korban Penipuan Transaksi Jual Beli Online Melalui Pidana Tambahan Ganti Kerugian Dalam Undang-Undang Informasi dan Transaksi Elektronik - Nyimas Enny Fitriya Wardhany; Iman Hidayat (Legalitas: Jurnal Hukum, 2025)
As a form of the state's commitment in responding to the development of information and communication technology, which has given rise to various forms of cybercrime, including fraud in online buying and selling transactions, the government enacted Law Number 19 of 2016 as an amendment to Law Number 11 of 2008 on Information and Electronic Transactions (ITE Law). This regulation serves as the main legal basis for combating crimes arising from the use of electronic systems, particularly online transaction fraud, which is governed by Article 28 paragraph (1) in conjunction with Article 45A paragraph (1) of the ITE Law. However, in practice, the ITE Law focuses more on punishing the perpetrators and does not yet provide comprehensive regulation regarding the protection of victims, especially concerning the provision of compensation in the form of restitution. Research results indicate that in various court decisions concerning online sales fraud cases, judges generally only impose the main criminal penalty on the perpetrators without ordering restitution payments to the victims. This is closely related to the fact that restitution is still considered optional within the Indonesian criminal law system, as reflected in the provisions of Articles 98–101 of the Criminal Procedure Code (KUHAP) and Article 1365 of the Civil Code (KUHPerdata), as well as the limitation of restitution to certain criminal acts under the Witness and Victim Protection Law. In fact, restitution is an important instrument in realizing restorative justice, which focuses on compensating the victims. Therefore, regulating restitution as a mandatory additional penalty under the Electronic Information and Transactions Law (UU ITE) becomes urgent to ensure that victims’ rights are fulfilled fairly and proportionately within the criminal justice system